Comparison of root canals obturated with ProTaper gutta-percha master point using the active lateral condensation and the single-cone techniques: a bacterial leakage study - Anizabele Milet do Amaral Mercês; Carlos Menezes Aguiar; Neide Kazue Sakugawa Shinohara; Andréa Cruz Câmara; Jose Antonio Poli de Figueiredo (Universidade Estadual de Campinas, 2015)
Aim: The aim of the present study was to assess the recontamination time of root canals filled with ProTaper gutta-percha master point using the active lateral condensation and the single-cone techniques. Methods: Fifty premolars, after biomechanical preparation, were randomly divided into six groups according to the obturation technique and the diameter of the gutta-percha point. For leakage evaluation, the roots were mounted in a dual-chamber leakage model system using Pseudomonas aeruginosa, Enterococcus faecalis, Escherichia coli, and Staphylococcus aureus. The Kaplan-Meier and Long-Rank tests were employed at the .05 level of significance. Results: The recontamination was detected between the 13th and 80th days. The active lateral condensation produced less infiltration than the single cone technique, though without statistically significant differences between them. Conclusions: It may be concluded that there was no difference in bacterial penetration between the two root canal filling techniques. The mean root canal contamination time was 67 days.